RISK MANAGEMENT PROCESS: PILLARS OF SUCCESS IN BUSINESS - Addin Hrp, Miftah Rizki; Haikal, M. Fikri; Sugianto, Sugianto (Proceeding International Seminar of Islamic Studies, 2024)
Risk management in the context of Islamic business is important in facing global challenges and ongoing economic changes. This is due to market complexity, economic uncertainty, currency fluctuations and various other risk factors that can affect the business. In addition, Islamic business principles demand different treatment in managing risk, with an emphasis on ethics and compliance with sharia. The aim of this research is to provide information about the risk management process using a literature review methodology, namely a research approach involved in the analysis, assessment and integration of texts relevant to a specific subject. There are four stages in the risk management process, namely risk identification, risk measurement. By applying risk management principles, organizations can reduce uncertainty, maintain sustainability, and achieve their goals more successfully.